Comparison of three type of muscle glycogen loading interventions using a very-high-carbohydrate diet in an elite male racewalker: a case report - Kondo, E.; Takai, E.; Sagayama, H.; Takahashi, H. (Physical Activity and Nutrition, 2023)
[Purpose] Muscle glycogen storage before a race is necessary for endurance athletes to achieve the best performance. Generally, the recommended carbohydrate intake for preparation over 90 min of the race is 10-12 g/kg/day. However, it remains unclear whether an elite athlete with an already high-carbohydrate diet can further increase muscle glycogen through a very-high-carbohydrate intake. Therefore, we compared the effects of three types of glycogen loading in a 28-year-old male athlete who belongs to the top 50 racewalkers in the world, consuming a daily energy intake of 4507 kcal and a carbohydrate intake of 12.7 g·g/kg/day.